Does Financial Inclusion Moderate CO2 Emissions in Sub-Saharan Africa? Evidence From Panel Data Analysis - Ogede, Jimoh S.; Tiamiyu, Hammed O. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
The threat posed by climate change has become a reality in the public sphere. This research looks at how financial inclusion affects carbon dioxide emissions in Sub-Saharan Africa (SSA) countries from 2004 to 2017. The panel autoregressive distributed lag and panel granger causality approaches are used to determine if financial inclusion reduces CO2 emissions in Sub-Saharan African countries. The PARDL results demonstrated that, over time, financial inclusion, GDP per capita, industrialization, and trade openness have a substantial beneficial influence on carbon emissions in SSA countries. The result suggests that these considered variables contribute significantly to CO2 emissions while urbanization and energy intensity reduce CO2 emissions in SSA. Financial inclusion and other control variables have no significant impacts on carbon emission in SSA in the short run. The findings of the granger causality test further confirm the direction of causality, revealing that financial inclusion, GDP per capita, industrialization, energy intensity, and trade openness, granger cause carbon emission in SSA countries. Meanwhile, carbon emission does not granger cause any of the considered factors. The study concludes that financial inclusion increases carbon emission in SSA countries, given the poor state of financial inclusion. Our findings advocate for a policy framework that would focus efforts on connecting financial inclusion measures with environmental legislation across SSA nations.